1981
DOI: 10.1192/bjp.139.3.181
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cognitive Therapy in Depression: A Treatment Trial Using Cognitive Therapy and Pharmacotherapy, each Alone and in Combination

Abstract: We report an extensive study which compares cognitive therapy, antidepressant drugs and a combination of these two, in depressed patients seen either in general practice or an out-patient department. One-hundred and forty patients were screened for primary major depression and 64 patients completed the trial. All were rated on seven measures of mood, including independent observer-rated and self-rated depression and scales of anxiety and irritability. Patients were randomly assigned to cognitive therapy, antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
182
0
5

Year Published

1982
1982
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(197 citation statements)
references
References 24 publications
9
182
0
5
Order By: Relevance
“…For depression studies, 21 studies were included [7,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] with 1,095 patients randomized to medication and 932 patients randomized to therapy. Forest plots of posttreatment CBT minus medication effect sizes are shown in Figures 2 and 3 for anxiety and depression, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For depression studies, 21 studies were included [7,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] with 1,095 patients randomized to medication and 932 patients randomized to therapy. Forest plots of posttreatment CBT minus medication effect sizes are shown in Figures 2 and 3 for anxiety and depression, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Gloaguen et al (1998) found that CBT was significantly better than antidepressant medication. This conclusion may overstate the case for CBT since Gloaguen et al (1998) included some early studies comparing CT with medications, which had methodological features that favored CT. One study (Rush, Beck, Kovacs, & Hollon, 1977) started tapering medications 1 week prior to the end of therapy, and another study (Blackburn, Bishop, Glen, Whalley, & Christie, 1981) was an effectiveness study in which the comparison group showed an unusually low response to medication. More recently, however, a major high-quality controlled trial comparing CT with a commonly prescribed serotonin reuptake inhibitor (paroxetine) found that cognitive therapy was equally effective for the initial treatment of moderate to severe major depression .…”
Section: Depressionmentioning
confidence: 99%
“…1. Thirty-five studies met inclusion criteria [2][3][4]5,6,8,[15][16][17][18]20,21,24,27,31,33,34,[40][41][42][43]45,46,[50][51][52][53][56][57][58][60][61][62]65,66]. Fig.…”
Section: Selection and Inclusion Of Studiesmentioning
confidence: 99%